An Acoustical Study of the Fricative /s/ in the Speech of Palestinian-speaking Broca's Asphasics – Preliminary Findings - Adam, Hisham (Linguistik online, 2013)
This study was conducted with four Palestinian-speaking Broca's aphasics and four normal speakers to examine the production of the fricative /s/ and to analyze the difference in acoustic patterns between the two groups. The acoustic analysis revealed that the Broca's aphasics were able to maintain the phonetic distinction between voiced and voiceless fricatives and did not exhibit voicing or devoicing errors. This result is inconsistent with findings from other languages. The spectral peak of the alveolar /s/ was lower for the aphasic subjects than for the control speakers. The Broca's aphasics displayed a longer duration for /s/ than the control subjects did. The /s/ spectra for the Broca's aphasics were "flatter" than the /s/ spectra for the control speakers and were characterized by a relatively low-frequency energy peak. Substitution errors predominated. In most cases, a one-distinctive-feature error occurred that primarily involved the place of articulation. Generally, the findings of the study suggest that the errors exhibited by Broca's aphasics reflect articulatory movements and articulatory implementation deficits rather than a selection of inappropriate speech segments.